2022
DOI: 10.1093/jcag/gwab047
|View full text |Cite
|
Sign up to set email alerts
|

Improving Colonoscopy Bowel Preparation and Reducing Patient Anxiety Through Recently Developed Online Information Resource: A Cross-sectional Study

Abstract: Introduction Invasive medical procedures such as colonoscopies can cause psychological distress and anxiety. Mycolonoscopy.ca is a multilanguage website that provides online written and video information (individual items reported in prior publications to be highly rated by patients) regarding preparation and what to expect before, during, and after colonoscopy. Information about how to access the website is included with all colonoscopy appointment materials in Winnipeg, Manitoba. We evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Our studies suggest the need to provide additional information to patients, highlighting the benefits of SDBP. We have recently reported how the use of an informative online platform is associated with an increased use of SDBP [33]. Our previous study that assessed patients' opinions about waking early for BP [32], found that almost three-quarters of patients did not This document was downloaded for personal use only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our studies suggest the need to provide additional information to patients, highlighting the benefits of SDBP. We have recently reported how the use of an informative online platform is associated with an increased use of SDBP [33]. Our previous study that assessed patients' opinions about waking early for BP [32], found that almost three-quarters of patients did not This document was downloaded for personal use only.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies suggest the need to provide additional information to patients, highlighting the benefits of SDBP. We have recently reported how the use of an informative online platform is associated with an increased use of SDBP [33].…”
Section: Original Articlementioning
confidence: 99%
“…Aims A successful colonoscopy requires ideal stool preparation, yet the percentage of insufficient bowel preparation is still very high. Frequently, the patients use website information on colonoscopy preparation 1 . Conversely, the daily activity of the hospital staff consists of spending time with patients, communicating with them and giving answers to a high number of questions coming from patients regarding the preparation for the procedure or the exam itself.…”
mentioning
confidence: 99%